Updates on traditional methods for combating malaria and emerging Wolbachia-based interventions - Mushtaq, Iqra; Sarwar, Muhammad Sajjad; Chaudhry, Ammara; Shah, Syed Ali Haider; Ahmad, Muhammad Mubeen (Frontiers in Cellular and Infection Microbiology, 2024)
The escalating challenge of malaria control necessitates innovative approaches that extend beyond traditional control strategies. This review explores the incorporation of traditional vector control techniques with emerging Wolbachia-based interventions. Wolbachia, a naturally occurring bacteria, offers a novel approach for combatting vector-borne diseases, including malaria, by reducing the mosquitoes’ ability to transmit these diseases. The study explores the rationale for this integration, presenting various case studies and pilot projects that have exhibited significant success. Employing a multi-dimensional approach that includes community mobilization, environmental modifications, and new biological methods, the paper posits that integrated efforts could mark a turning point in the struggle against malaria. Our findings indicate that incorporating Wolbachia-based strategies into existing vector management programs not only is feasible but also heightens the efficacy of malaria control initiatives in different countries especially in Pakistan. The paper concludes that continued research and international collaboration are imperative for translating these promising methods from the laboratory to the field, thereby offering a more sustainable and effective malaria control strategy.